The Current State of the Art in Acute Kidney Injury - Devarajan, Prasad (Frontiers in Pediatrics, 2020)
Decades of pre-clinical research have uncovered biologic pathways and mechanisms that have suggested promising therapeutic approaches for acute kidney injury (AKI) in animal models. However, translational efforts in human AKI have uniformly yielded disappointing results. Fortunately, recent discoveries in AKI molecular mechanisms are providing new opportunities for early detection and novel interventions. This review identifies technologies that are revealing the exceptionally complex nature of the normal kidney, the remarkable heterogeneity of the AKI syndrome, and the myriad responses of the kidney to AKI. Based on the current state of the art, novel approaches to improve the bench to bedside translation of novel discoveries are proposed. These strategies include the use of unbiased approaches to improve our understanding of human AKI; establishment of irrefutable biologic plausibility for proposed biomarkers and therapies; identification of patients at risk for AKI pre-injury using clinical scores and non-invasive biomarkers; initiation of safe and effective preventive interventions pre-injury in susceptible patients; early identification of patients who are at risk for AKI post-injury using electronic health record triggers, clinical scores and novel biomarkers; employment of sequential biomarkers to initiate appropriate therapies based on knowledge of underlying pathophysiology; use of new biomarkers as criteria for enrollment in randomized clinical trials, assessing efficacy, and empowering the drug development process; and early initiation of anti-fibrotic therapies. These strategies are immediately actionable and hold tremendous promise for effective bench-to-bedside translation of novel discoveries that will change the current dismal prognosis of human AKI.